Evaluation of the quality of blood components obtained after automated separation of whole blood by a new multiunit processor. Issue 8 (11th December 2012) - Lagerberg, Johan W.; Salado‐Jimena, Jose A.; Löf, Helena; Bontekoe, Ido J.; Nielsen, Connie; Verheggen, Caroline; van, Geert; van der, Pieter F.; de, Dirk; Hansen, Morten B.; Knutson, Folke
<x xml:space="preserve">Abstract</x> Background The Reveos system (Terumo BCT) is a fully automated device able to process four whole blood (WB) units simultaneously into a plasma unit, a red blood cell (RBC) unit, and an interim platelet (PLT) unit (IPU). Multiple IPUs can be pooled to form a transfusable PLT product. The aim of our study was to evaluate the quality of components made with the Reveos system from either fresh (2‐8 hr) or overnight‐held WB. Study Design and Methods A prototype of the Reveos system was used to process WB. RBCs were resuspended in SAGM, leukoreduced, and assayed for in vitro quality variables during a 42‐day storage period at 2 to 6°C. Twenty‐four‐hour in vivo recovery was determined on Day 42. Plasma was assayed for cellular contamination and activation variables. IPUs were pooled with SSP+ additive solution for in vitro quality assessments during a 7‐day storage period at room temperature. Results Reveos‐produced RBCs and plasma units met the predefined requirements. RBC recovery was superior to control units. On Day 42, hemolysis was below 0.8% and in vivo recovery was above 75% for all RBCs. Cellular contamination was lower for Reveos‐produced plasma. PLT yield was higher with overnight‐stored WB. PLT quality was well maintained during storage with no significant differences between the two groups. Conclusion Blood components prepared with the Reveos from fresh or overnight‐held WB meet quality criteria without any relevant difference between the two groups. The Reveos system has the potential to increase efficacy and standardization of blood component preparation.